2020
DOI: 10.1002/ece3.6047
|View full text |Cite
|
Sign up to set email alerts
|

Artificial reef design affects benthic secondary productivity and provision of functional habitat

Abstract: Novel hard substratum, introduced through offshore developments, can provide habitat for marine species and thereby function as an artificial reef. To predict the ecological consequences of deploying offshore infrastructure, and sustainably manage the installation of new structures, interactions between artificial reefs and marine ecosystem functions and services must be understood. This requires quantitative data on the relationships between secondary productivity and artificial reef design, across all trophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 53 publications
(63 reference statements)
0
18
0
Order By: Relevance
“…The design of ARs could be adjusted to reduce the effect of illegal fishing by passively preventing both industrial and artisanal fishing activity. Complex structures are more effective for fish production and attraction 27 . We showed that, although production might have a limited effect on total catch, attraction can largely increase AR efficiency (total catch) if the rate of illegal fishing rate is very low or absent.…”
Section: Discussionmentioning
confidence: 99%
“…The design of ARs could be adjusted to reduce the effect of illegal fishing by passively preventing both industrial and artisanal fishing activity. Complex structures are more effective for fish production and attraction 27 . We showed that, although production might have a limited effect on total catch, attraction can largely increase AR efficiency (total catch) if the rate of illegal fishing rate is very low or absent.…”
Section: Discussionmentioning
confidence: 99%
“…However, the design of ARs could be adjusted to reduce the effect of illegal shing by passively preventing both industrial and artisanal shing activity. Complex structures are more effective for sh production and attraction 23 . We showed that, although production might have a limited effect on total catch, attraction can largely increase AR e ciency (total catch) if the rate of illegal shing rate is very low or absent.…”
Section: Discussionmentioning
confidence: 99%
“…mercury, arsenic, hereafter referred to as metals), residual hydrocarbons and naturally occurring radioactive materials (NORM; Supplementary Figure 1). Such impacts may include reduced fishery productivity and the discharge of contaminants creating localized waters and sediments enriched in contaminants; with the latter having potential negative implications to marine biota (Almeda et al, 2014;Johannessen et al, 2007;Rouse et al, 2020). Even with the projected largescale decommissioning of infrastructure, the long-term environmental impacts from metals and NORMs are often overlooked.…”
Section: Decommissioning Of Oil and Gas Infrastructurementioning
confidence: 99%